Many refugees have work experience but a smaller share possess formal vocational qualifications - Elisabeth Liebau; Zerrin Salikutluk (DIW Economic Bulletin, 2016)
Academic and vocational qualifications play a crucial role when it comes to successfully integrating refugees and other migrants into society. What qualifications did migrants already acquire in their country of origin and which did they obtain in Germany? And to what extent are qualifications gained abroad recognized in Germany? The IAB-SOEP Migration Sample shows that the majority of the migrant groups studied in the present report completed their schooling abroad and already gained professional experience there. However, only a smaller share possess formal vocational qualifications. One-third of refugees and other migrants applied for foreign qualifications to be recognized in Germany. Hoewever, the recognition rate is low for refugees. For migrants to find work in Germany, it is crucial that the qualifications they bring with them are in demand on the German labor market. On the one hand, it is important that they learn German and invest in further training programs, and on the other, they should seek recognition of their academic and vocational certificates in Germany.
Keywords: F22; I21; I28; J24; 330; refugees; education acquisition; human capital; recognition of foreign degrees